The effects of altitude training on sea-level swimming performance
This study used two groups of six "B" level swimmers, one training at altitude, the other at sea-level, for 30 days. Because of these small group numbers, it is hard to be conclusive about the findings. There were a number of factors that should be considered. 1. High-volume training cannot and should not be done during the first four days at altitude. 2. It usually takes seven days for swimmers to begin to feel better ("normal"). 3. By the tenth day swimmers should be able to perform the same repeat sets as done at sea-level, although performances may be slower. 4. Lactate tolerance training should be emphasized to the same amount or even more in altitude programs. This should commence after 10 days. The reduced work volume at altitude necessitates this compensatory programming. 5. Iron supplementation at altitude may be beneficial. 6. The study concluded: Fast performances can be achieved either within the first four days of sea-level reexposure or after 14 days. Racing in the first four days at sea-level requires that a taper be done at altitude. Racing after 14 days allows for a sea-level taper.